Limited Liability and Justice: When Should We Pierce the Corporate Veil? - Sebastiani, Andrea (Mae Fah Luang University Law Journal, 2021)
Over the years, it has become common practice for some shareholders to use the limited liability of companies in such a way in order to cheat in pursuit of their personal interests. Various theories have been developed to address this issue, several of which give indication as to when judges should disregard shareholder’s limited liability - although recognized by law. These theories are known under the name of piercing the corporate veil. The present article will analyze some among the most relevant of these theories, taking into consideration the solutions adopted in various legal systems. In particular, the German, Italian, Chinese, English and US legal systems were taken into consideration due to the innovative nature of the theories they introduced. Moreover, the great disparities between these systems, facilitate the comparison between the solutions offered in order to deal with the issue of veil piercing. Finally, a reworked of veil piercing and the policy implications are proposed.